A role for haemolymph oxygen capacity in heat tolerance of eurythermal crabs - Giomi, Folco; Poertner, Hans O. (Frontiers in Physiology, 2013)
Heat tolerance in aquatic ectotherms is constrained by a mismatch, occurring at high temperatures, between oxygen delivery and demand which compromises the maintenance of aerobic scope. The present study analyses how the wide thermal tolerance range of an eurythermal model species, the green crab Carcinus maenas is supported and limited by its ability to sustain efficient oxygen transport to tissues. Similar to other eurytherms, C. maenas sustains naturally occurring acute warming events through the integrated response of circulatory and respiratory systems. The response of C. maenas to warming is characterized by two phases. During initial warming, oxygen consumption and heart rate increase while stroke volume and haemolymph oxygen partial pressures decrease. During further warming, dissolved oxygen levels in the venous compartment decrease below the threshold of full haemocyanin oxygen saturation. The progressive release of haemocyanin bound oxygen with further warming follows an exponential pattern, thereby saving energy in oxygen transport and causing an associated leveling off of metabolic rate. According to the concept of oxygen and capacity limited thermal tolerance, this indicates that the thermal tolerance window is widened by the increasing contribution of haemocyanin oxygen transport and associated energy savings in cardiocirculation. Haemocyanin bound oxygen sustains cardiac performance to cover the temperature range experienced by C. maenas in the field. To our knowledge this is the first study providing evidence of a relationship between thermal tolerance and blood (haemolymph) oxygen transport in eurythermal invertebrates.